Análise da adesão ao tratamento em mulheres com lúpus eritematoso sistêmico - NEDER, Patrícia Regina Bastos (Universidade Federal do Pará, 2014)
Systemic lupus erythematosus (SLE) is a chronic autoimmune, multisystemic connective tissue inflammatory disease, capable of affecting several organs and systems throughout the body. It affects mostly women and presents periods of remission and exacerbation. Even though its etiology still unknown, several factors contribute to the development of the disease, among them hormonal, environmental, genetic and immunological factors. Some clinical manifestations have challenged the specialists, among them the association of SLE with depressive states. This study aimed to identify related variables with adhesion to treatment in women with SLE diagnosis. Correlations were made between socio demographic characteristics, levels of depression, quality of life, coping and adhesion behavior to treatment strategies. The following instruments were used: Itineraries of interview, The Beck Scale, International Quality of Life Assessment Project (SF-36), The Ways of Coping Scale, World Health Organization Quality of Life Assessment (WHOQOL-BREF). The participants formed a group of thirty patients attended at the rheumatology ward of a public hospital. They were distributed in two groups: Adhesion (n=17) and Non Adhesion (n=13). The adhesion group, regardless of age and time of diagnosis, presented lower levels of depression when compared with the non adhesion group. The results suggest that, on both groups, during the first five months of patients’ coexistence with SLE, the physical aspect, pain and the general state of health are found to be difficult factors to deal with. However, it is possible to assert that, in the same period, if the patient does not adhere to the medical prescriptions, the discomfort regarding the mentioned factors is intensified. The correlation between Vitality subscale and the social Aspects (measured by the SF-36) and the adhesion to treatment presented valid results, for the Adhesion group participants also reported that they felt protected as much by their social group as by the health team. The results suggest that depressive behavior can take place for the long period these patients have been living with the uncontrollability of the disease symptoms, and also for the sequelae caused by SLE, which affects them severely, implicating vital organs such as kidneys, heart, lungs, damaging their quality of life. The pros and cons, as well the limitations on the use of instruments for identification of relevant variables in the study of adhesion to the treatment in chronic diseases are also discussed. Longitudinal studies are suggested, with delineation of the subject as its own control to investigate the relation between depressive states, control of symptoms and adhesion to treatment.